Medial pivot total knee arthroplasty for valgus knees provides equivalent medial stability compared to that for varus knees: In vivo kinematic study - Tomofumi Kage; Kenichi Kono; Tetsuya Tomita; Takaharu Yamazaki; Shuji Taketomi; Ryota Yamagami; Kohei Kawaguchi; Ryo Murakami; Takahiro Arakawa; Takashi Kobayashi; Hiroshi Inui; Sakae Tanaka (Journal of Experimental Orthopaedics)
Abstract Purpose The efficacy of medial pivot total knee arthroplasty (MP TKA) in treating valgus knees that may cause medial instability is unknown. The purpose of this study was to investigate the in vivo kinematics of MP TKA for the valgus knees and compare them to those for the varus knees. Methods The kinematics of 19 valgus knees and 19 varus knees operated in the MP TKA were investigated under fluoroscopy during squatting using a two‐ to three‐dimensional registration technique. Accordingly, the valgus and varus knees were evaluated and compared in terms of knee flexion angle, anteroposterior translation for the medial and lateral low contact points, axial rotation and valgus–varus angle of the femoral component relative to the tibial component, as well as kinematic pathways. Results The knee flexion angle was found to be identical in both knees. There was no anterior translation on the medial side of the valgus knees, and no difference was detected between the two knees. On the lateral side, posterior translation was observed in both knees, with no difference between the two. Femoral external rotation was observed in both knees, and no difference was detected between the two. There was no valgus–varus change in the valgus knees, nor was there a difference between the two knees. The valgus knees demonstrated MP motion, whereas the varus knees demonstrated MP motion and bicondylar rollback. Conclusion The medial side of the valgus knees treated with MP TKA showed comparable stable kinematics to the varus knees. The MP TKA is an effective procedure for valgus knees to stabilize the medial compartment. Level of Evidence Level Ⅲ.